2010
DOI: 10.1590/s0103-84782010000600030
|View full text |Cite
|
Sign up to set email alerts
|

Seed treatment affects Meloidogyne incognita penetration, colonization and reproduction on cotton

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Nematicidal formulations based on the active ingredient abamectin (avermectins) have been developed specifically for seed applications. The efficiency of abamectin was first reported in the control of M. incognita in cotton (MONFORT et al, 2006), tomato (FASKE;, and melon (MOREIRA et al, 2004); when applied at relatively low doses in the seed treatment, the active ingredient interacts with the tegument and interferes with the nematode population around it (FASKE;BESSI et al, 2010;CORTE et al, 2014). Other studies, however, indicate that seed treatment with nematicides offers good prospects when integrated with other measures within phytonematode management (FAVORETTO et al, 2010;STEFFEN et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nematicidal formulations based on the active ingredient abamectin (avermectins) have been developed specifically for seed applications. The efficiency of abamectin was first reported in the control of M. incognita in cotton (MONFORT et al, 2006), tomato (FASKE;, and melon (MOREIRA et al, 2004); when applied at relatively low doses in the seed treatment, the active ingredient interacts with the tegument and interferes with the nematode population around it (FASKE;BESSI et al, 2010;CORTE et al, 2014). Other studies, however, indicate that seed treatment with nematicides offers good prospects when integrated with other measures within phytonematode management (FAVORETTO et al, 2010;STEFFEN et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Faske and Starr (2007) also explained that abamectin is concentrated in the seed tegument, and as the roots develop beyond this protective region, they are exposed to nematode attack. Moreover, seed treatment promotes greater root system development, which becomes a very efficient nutritional source for nematodes, resulting in increased nematode populations at the end of the crop cycle (BESSI et al, 2010). However, the control of the nematode population in the initial phase of the crop is fundamental to ensure protection and realization of the yield potential of the crop (OLIVEIRA et al, 1999;GALBIERI et al, 2007).…”
mentioning
confidence: 99%
“…Among the naturally occurring bio nematicides are avermectins. These are a family of 16 membered macrocyclic lactones produced by the soil microorganism, Streptomyces avermitilis (Bessi et al, 2010). These compounds are important tools in animal health and crop protection, the major component of the fermentation being avermectin B1 (Abamectin) (Rehman, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are important tools in animal health and crop protection, the major component of the fermentation being avermectin B1 (Abamectin) (Rehman, 2009). A number of success cases in abamectin controlling nematodes have been reported in tomatoes and cotton seed treatments (Becker, 1999;Monfort et al, 2006;Faske and Starr, 2006;Rehman, 2009;Alfonso et al, 2009: Bessi et al, 2010DeBeer, 2010). Chen et al (2006) demonstrated the enhancement of a bio agent Pochonia in reducing nematode damage in vines with a resultant increase in plant dry weight and height.…”
Section: Introductionmentioning
confidence: 99%
“…Seed treatment with nematicides has also been suggested to control P. brachyurus. According to Bessi et al [44], seed treatment with nematicides can be an effective control method for this nematode, since it avoids damage in early stages of plant development, which stimulates the development of roots and minimizes the effect in case of drought stress. Several studies reported the effect of the seed treatment in reducing P. brachyurus population level in soybean [45].…”
Section: Root Lesion Nematode (P Brachyurus)mentioning
confidence: 99%